Cognitive insight and verbal learning in schizophrenia - Lua, Chong Teck (2015)

(untitled)
Background: Schizophrenia is a disorder with frequent relapses due to impaired insight which is poorly understood. Clinical insight is the usual insight assessment but patients with good clinical insight could still relapse. A different concept of insight called cognitive insight has been introduced to complement clinical insight. It assesses the ability to reappraise and modify abnormal thoughts or beliefs, and severe psychosis affects cognitive insight. Despite both insights being different, they are part of the neurocognitive model of insight. Relationships between cognitive insight and verbal learning (working memory; a neurocognitive domain), have been shown. Good verbal learning, therefore, plays a role to improve patient’s insight and receive better psychosocial intervention to prevent relapse. Objectives: To evaluate the relationship between cognitive insight with verbal learning, clinical insight and severity of psychopathology, as well as determining other associated factors of insight among patients with schizophrenia at Kota Bharu, Kelantan. Methodology: This cross-sectional study recruited 108 outpatients with schizophrenia from two tertiary hospitals using convenience sampling method. Patients self-rate the Beck Cognitive Insight Scale (BCIS) questionnaire and were interviewed by a researcher for clinical insight and severity of psychopathology. Verbal learning tests were conducted to assess working memory. Relationships between cognitive insight with verbal learning, clinical insight and severity of sychopathology were determined by correlation analyses. Multiple linear regression analyses (MLR) were done to identify other associated factors of insight. Results: Majority were males, single and unemployed. Mean BCIS scores for three domains were: BCIS-SR 12.52 (SD=4.62), BCIS-SC 8.93(SD=3.45) and BCISComposite 3.57(SD=4.92). Correlation analyses showed no significant results. In MLR, BCIS-Composite was significantly associated with females, who showed 1.99 units higher in BCIS-Composite than males. Better clinical insight was significantly associated with primary school educational status (p=0.018), duration of illness (p<0.001) and delayed recall capability in verbal learning (p=0.006). Conclusion: This early study revealed no relationship between cognitive insight with verbal learning, clinical insight and severity of psychopathology, but found significant positive association with female gender. Unlike cognitive insight, the gender factor did not predict better clinical insight but was instead associated with the educational status, illness duration and delayed recall of verbal learning. Therefore, both types of insight are independently contributed by different factors despite being in the same spectrum and theoretical model of insight. More research needs to be conducted to tap into the new interest area of cognitive insight.